2019
DOI: 10.1002/chem.201903215
|View full text |Cite
|
Sign up to set email alerts
|

C−H and C−M Activation, Aromaticity Tuning, and Co⋅⋅⋅Ru Interactions Confined in the Azuliporphyrin Framework

Abstract: Taking advantage of the specific properties of azuliporphyrin and the reactivity of cobalt(II), activation of an azulene C(sp2)−H bond occurred and organometallic complexes with Co−C bonding were formed. The system allowed for macrocyclic aromaticity tuning through metal coordination and oxidation. Thanks to the CoII−C and parallel tested CuII−C reactivity and the affinity of metal centers to dioxygen, oxygen atom insertion into the M−C bond could be investigated. Insertion starts with an oxygen molecule coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Regular cobalt(II) azuliporphyrin S78-1 (Scheme 78) forms smoothly in a reaction of azuliporphyrin S64-2 and cobalt(II) salts. 196 The complete insertion occurs, inferring the activation of the C( 21 Due to the incorporation of the oxygen bridge in S78-4, the azulene moiety is even more deflected from the porphyrin plane, which forces even closer contact between metal centres, compared to S78-2, with a Co II Á Á ÁRu 0 distance of 2.9799( 12) Å (Fig. 18).…”
Section: Coordination Of Fused 21-carbaporphyrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular cobalt(II) azuliporphyrin S78-1 (Scheme 78) forms smoothly in a reaction of azuliporphyrin S64-2 and cobalt(II) salts. 196 The complete insertion occurs, inferring the activation of the C( 21 Due to the incorporation of the oxygen bridge in S78-4, the azulene moiety is even more deflected from the porphyrin plane, which forces even closer contact between metal centres, compared to S78-2, with a Co II Á Á ÁRu 0 distance of 2.9799( 12) Å (Fig. 18).…”
Section: Coordination Of Fused 21-carbaporphyrinsmentioning
confidence: 99%
“…Such a hypothesis was tested and indeed, under strictly anaerobic conditions, without an excess of the copper( ii ) source, appropriate species S70-1 (Scheme 70) is obtained. 196 This elusive, very reactive form, trapped by EPR spectroscopy, transforms into S70-2 as soon as exposed to dioxygen, reflecting the incorporation of an oxygen atom into the extremely sensitive Cu II –C(21) bond. The acidic demetallation of S70-2 afforded 21-hydroxyazuliporphyrin S70-3 , but in solution, its oxo tautomer S70-4 (identified in the solid state – C(21)O 1.268(3) Å) prevails.…”
Section: Azuliporphyrin and Benzocarbaporphyrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions in the presence of 18 O 2 demonstrated that the oxygen atom derives from molecular oxygen. A recent study demonstrated that copper(II) complex 205 can be isolated under strictly anaerobic conditions using a glove box [ 172 ]. Exposure to air then led to the formation of 204 .…”
Section: Organometallic Chemistry Of Azuliporphyrinsmentioning
confidence: 99%
“…In contrast to meso -unsubstituted azuliporphyrins, tetraphenylazuliporphyrin 202 reacted with CoCl 2 or Co(OAc) 2 to give cobalt(II) azuliporphyrin 215 ( Scheme 35 ) [ 172 ]. In addition, treatment of 202 with Co 2 (CO) 8 afforded a transient π-allyl complex 216 that slowly converted into 215 .…”
Section: Organometallic Chemistry Of Azuliporphyrinsmentioning
confidence: 99%